Major Gaps in Sterba's New Atheological Argument from Evil - Collins, M. Robin (Religions, 2022)
In this essay, I first offer several scenarios where Sterba’s argument based on the Pauline Principle fails: specifically, one in which we all consent to living an earthly life in some prior existence (prior-consent scenario), one in which the victims would approve of the evil being done to them for some greater good (would-approve scenario), and one that combines one of these two scenarios with the stipulation that the greater goods redound to the victims (victim-beneficiary scenario). Along the way, I claim that a version of the Kantian principle that persons should not be treated as mere means, but as ends in themselves, better captures the intuitions used in support of the Pauline Principle. After this, I present two further significant problems with Sterba’s arguments. First, I argue that his claim that God should prevent the serious evil consequences of our free choices fails to consider the degree to which such a policy would make us aware of God’s monitoring of our every move. This in turn would greatly diminish our ability to make morally significant choices. Second, I point out flaws with his argument for the applicability of the Pauline Principle to God’s choices, particularly objecting to his argument that any greater-good theodicy implies that God would desire that people sin so that good may come, something he claims is morally perverse.